Pengaruh Foto Profil dan Cover pada Jejaring Sosial Facebook dalam Membentuk Personal Branding: Studi Kasus Mahasiswa dan Alumni FSRD Universitas Trisakti - Franzia, Elda (Bina Nusantara University, 2015)
The need of personal branding development of Indonesian people from various professions has been increasing for self positioning in social and professional states. Students and alumni of Faculty of Art and Design Trisakti University as Indonesian young designers in global market use social media to develop their personal branding, especially from personal identity showed in account?s name, profile picture, and cover photo in personal account in Facebook. Respondents in this research were 40 students and alumni of Faculty of Art and Design Trisakti University with visual data collected by documentation method from Facebook accounts. Research used combination of quantitative and qualitative methods. The quantitative method was used to define respondents? behavior tendency in forming their personal branding, and the qualitative method was used to define profile picture and cover photo usage in forming respondents? personal branding. The result of this research is the understanding of the profile picture and cover photo usage in forming personal branding and the understanding of visual elements usage in effective visual communication to endorse the development of personal branding for Indonesian young designers.